Self-Help Plus for Refugees and Asylum Seekers: An Individual Participant Data Meta-Analysis - Eirini Karyotaki, Marit Sijbrandij, Marianna Purgato, Lakin Daniel, Leku Marx Ronald, Corrado Barbui (BMJ Ment Health, 2023)
Refugees and asylum seekers are at high risk of mental disorders due to various stressors before, during and after forceful displacement. The WHO Self-Help Plus (SH+) intervention was developed to manage psychological distress and a broad range of mental health symptoms in vulnerable populations. This study aimed to examine the effects and moderators of SH+ compared with Enhanced Care as Usual (ECAU) in reducing depressive symptoms among refugees and asylum seekers